Characteristics of Serial Verb Construction of Thai Sentences with Semantic Similarity to Prepositional Phrase 把 in Chinese: คุณลักษณะความเป็นหน่วยสร้างกริยาเรียงของประโยคภาษาไทยที่เป็นคู่เทียบความหมายของ หน่วยสร้างบุพบทวลี 把ในภาษาจีน - Tiyanon, Nuttanun; Theerapojjanee, Theerawat (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2023)
The preposition 把 is a complete Chinese preposition that has undergone grammaticalisation of verb. In other words, there is no usage of 把 as a general verb in modern Chinese communication. When translating the prepositional phrase 把 into Thai, a Thai verb such as เอา (to take) is added in the position where 把 occurs in order to convey the source structure and meaning. However, the prepositional phrase construction 把 can convey various meanings, some of which are not equivalent to เอา (to take). The relative structure and meaning of เอา in Thai may be treated as serial verb construction. Nonetheless, some prepositional phrase construction 把 cannot be treated as serial verb construction where the verb เอา acts as the first verb, as it can affect the perception and understanding of such construction. The purposes of this research study are 1) to investigate characteristics of serial verb construction of Thai sentences with semantic similarity to the prepositional phrase 把 in various meanings by characterizing shared features, classifying meanings of the prepositional phrase 把 based on the book “现代汉语八百词” (Modern Chinese 800 Words, 1980), and reanalyzing each group of meanings based on the features of serial verb prototype; and 2) to propose useful ways to understand the meaning of prepositional phrase 把 in Chinese through the concept of Thai serial verb construction. The findings reveal that the meaning of preposition phrase 把 is comparable to the Thai serial verb construction that conveys displacement and causative meanings. The displacement meaning of prepositional phrase 把 is comparable to the Thai serial verb construction prototype, and the causative meaning can be comparable to both serial verb construction prototype and non-prototype in Thai language. However, the disposal meaning of prepositional phrase 把 is not comparable to any serial verb construction in Thai language, as the verb relatively appears in one position in the Thai structure which is not a fundamental characteristic of serial verb construction.